Prenatal androgen receptor activation determines adult alcohol and water drinking in a sex-specific way - Huber, Sabine; Zoicas, Iulia; Reichel, Martin; Mühle, Christiane; Büttner, Christian; Ekici, Arif Bülent; Eulenburg, Volker; Lenz, Bernd; Kornhuber, Johannes; Müller, Christian P. (Addiction Biology, 2017)
Alcohol use disorders are major psychiatric disorders. Correlational studies in humans suggested organizational hormonal effects during embryonic development as a risk factor for adult alcohol dependence. Permanent changes can be induced by the activity of sex hormones, like testosterone. Here, we demonstrate a relationship between prenatal androgen receptor (AR)-activation and adult alcohol as well as water drinking in mice in a sex-dependent fashion. Prenatal AR inhibition using the antagonist flutamide decreased adult male alcohol consumption. In contrast, prenatal AR activation by dihydrotestosterone (DHT) led to an increase in adult alcohol consumption in females. These effects were different in adult water drinking, flutamide increased water consumption in females and DHT increased water consumption in males. Prenatal flutamide reduced locomotion and anxiety in adult males but was ineffective in females. We found that prenatal AR activation controls adult levels of monoaminergic modulatory transmitters in the brain and blood hormone levels in a sex-specific way. RNA-Seq analysis confirmed a prenatal AR mediated control of adult expression of alcohol drinking-related genes like Bdnf and Per2. These findings demonstrate that prenatal androgen activity is a risk factor for the establishment of alcohol consumption in adults by its organizational effects.
EVALuna2:4035